Accountability Analysis of Village Financial Management (Case Study in Manulea Village, Sasitamean District, Malaka Regency) - Taek, Apriyani Yuninda; Sopanah, Ana; Fatoni, Irfan (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This research aims to explore and analyze financial management at the village level, with a focus on transparency and accountability in budget use. In this context, villages as indonesia’s smallest government entities have and important role in developing a just and prosperous society. This research method used is a descriptive qualitative approach, which includes data collection through interviews whih the community and village officials. Interview results show that the community feels less involved in monitoring budget use, even though there are village meetings that involve them planning activities, in addition, the village secretary, explained his responsibilities in ensuring financial reports are accurate and in accordance with applicable regulations, as well as the importance of supervision from the community to increase accountability. This research includes theories relevant to public financial management and public sector accounting, which emphasizes the importance of transparency in managing village funds. It is hoped that this research can contribute to understanting the dynamics of financial menegement in villages and encourage community participation in budget monitoring, so as to create a more accountable and transparent village government.